Global Three‐Dimensional Simulation of Earth's Dayside Reconnection Using a Two‐Way Coupled Magnetohydrodynamics With Embedded Particle‐in‐Cell Model: Initial Results. Issue 10 (21st October 2017) - Chen, Yuxi; Tóth, Gábor; Cassak, Paul; Jia, Xianzhe; Gombosi, Tamas I.; Slavin, James A.; Markidis, Stefano; Peng, Ivy Bo; Jordanova, Vania K.; Henderson, Michael G.
Abstract: We perform a three‐dimensional (3‐D) global simulation of Earth's magnetosphere with kinetic reconnection physics to study the flux transfer events (FTEs) and dayside magnetic reconnection with the recently developed magnetohydrodynamics with embedded particle‐in‐cell model. During the 1 h long simulation, the FTEs are generated quasi‐periodically near the subsolar point and move toward the poles. We find that the magnetic field signature of FTEs at their early formation stage is similar to a "crater FTE, " which is characterized by a magnetic field strength dip at the FTE center. After the FTE core field grows to a significant value, it becomes an FTE with typical flux rope structure. When an FTE moves across the cusp, reconnection between the FTE field lines and the cusp field lines can dissipate the FTE. The kinetic features are also captured by our model. A crescent electron phase space distribution is found near the reconnection site. A similar distribution is found for ions at the location where the Larmor electric field appears. The lower hybrid drift instability (LHDI) along the current sheet direction also arises at the interface of magnetosheath and magnetosphere plasma. The LHDI electric field is about 8 mV/m, and its dominant wavelength relative to the electron gyroradius agrees reasonably with Magnetospheric Multiscale (MMS) observations. Key Points: We performed a 1 h long global simulation of Earth's magnetosphere with kinetic modeling of the dayside reconnection Crater FTE is found at the early stage of a flux rope formation Kinetic phenomena are found from the global simulation